Determinants of Failure and Resilience: A Holistic Analysis of Beed Graduates’ Experiences in the Licensure Examination for Professional Teachers - Zydrick L Avelino; Jaime M Forbes; Josie Anne R Tamaño; Mark Hardby M Belanio (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: High failure rates in the Licensure Examination for Teachers (LET), particularly among Bachelor of Elementary Education graduates, present a persistent challenge to the Philippine education system. This study aimed to determine the interlocking personal, academic, and institutional factors influencing repeated failure and to develop a holistic LET Readiness Framework integrating cognitive, emotional, and contextual dimensions. Methodology: The study utilized a mixed-methods research design involving BEEd graduates. Quantitative data were analyzed using descriptive statistics and Spearman’s rho correlation via SPSS and Jamovi to examine the relationship between General Education and Professional Education performance. Qualitative data were gathered through semi-structured interviews and analyzed using the CAQDA tool, Quirkos, to identify thematic patterns in examinee experiences. Main Findings: The study concludes that repeated LET failure stems from a complex interplay of academic, emotional, and contextual experiences. Quantitative analysis confirmed that scores in the Professional Education component were consistently lower than those in General Education, reaffirming a critical academic weakness. Qualitative findings highlighted significant psycho-emotional challenges among examinees, including stress, self-doubt, and financial hardship. Participants' trajectories were also shaped by their internal coping mechanisms, their attributions for failure, and the availability of support systems. These factors were synthesized into a proposed LET Readiness Framework grounded in psychological theory. Novelty/Originality of this study: The research introduces a novel Holistic LET Readiness Framework that synthesizes Self-Efficacy, Attribution, and Self-Regulated Learning theories. It advances understanding by integrating academic, emotional, and institutional dimensions, offering a data-informed, human-centered model for teacher education institutions and policymakers.